The Effectiveness of Bay Leaf Extract (Eugenia polyantha) on the Stamina Enhancement of Male Mice (Mus musculus) - Izzati, Dalilah Sofiah; Maretha, Delima Engga (El-Hayah:Jurnal Biologi, 2025)
Bay leaves are a common culinary spice used in Indonesian cuisine and are known to contain various chemical compounds including essential oils, flavonoids, tannins, antimicrobial compounds, and vitamin C. This study aims to investigate the effectiveness of bay leaf extract in enhancing the stamina of male mice. The research was conducted using a quantitative experimental method with a completely randomised design (CRD). A total of 20 male mice were used as samples and divided into five treatment groups, which included a control group (P0), a dosage of 3 mg/g body weight (P1), a dosage of 6 mg/g body weight (P2), a dosage of 12 mg/g body weight (P3), and a dosage of 18 mg/g body weight (P4), with each treatment repeated three times. The swimming test was employed to measure the duration of swimming in mice as an indicator of stamina. Data were analysed using ANOVA. The results indicated that the administration of bay leaf extract at various doses over a period of 7 days did not produce a significant (P=0,715) effect on the stamina enhancement of male mice. Therefore, bay leaf extract was not effective in improving the stamina of male mice at the tested dosages.